(untitled) (Arquivos Catarinenses de Medicina, 2024)
Objetivo: Analisar o perfil clínico, epidemiológico, laboratorial e desfecho dos pacientes na faixa etária de 0 a 15 anos incompletos, internados com diagnóstico confirmado de COVID-19. Metodologia: Estudo transversal, quantitativo, retrospectivo, através de coleta de dados de pacientes de 0-5 anos incompletos, internados com diagnóstico laboratorial confirmado de COVID-19, em um hospital infantil no sul do Brasil, no período de 1º de junho de 2020 a 31 de maio de 2021, utilizando informações de fichas da SIVEP-gripe e fichas de notificação compulsória do Estado de Santa Catarina. Resultados: Dos 69 pacientes internados com COVID-19, 50,7% eram do sexo feminino, com idade média de 4,04 anos. Os sintomas leves foram mais encontrados 72,9% (n=41), sintomas predominantes foram febre 73,7% (n=28), tosse 60,5% (n=23) e coriza 73,7% (n=28). A maioria ficou internada em leito de enfermaria 78,2% (n=54) e teve alta hospitalar, outros 20,8% (n=15) necessitavam de leito de UTI. Dos pacientes internados em UTI, apresentaram sintomas moderado/graves/críticos 21% (n=13) e desses (n=2) evoluíram para o óbito. Conclusion: The most affected age group was 0 to 3 years old, and female. The mildest respiratory symptoms were the most common, with fever and cough being the most prevalent, only 2 patients died. Laboratory tests showed a predominance of leukocytosis and lymphopenia, and increased C-reactive protein. In imaging exams, there was a predominance of diffuse interstitial infiltrates, followed by ground-glass opacity, especially in patients who were in the UTI. Palavras-chaves: COVID-19, infecção respiratória, pediatria, SARS-CoV-2, epidemiologia. Objective: To analyze the clinical, epidemiological, laboratory profile and outcome of patients aged 0 to 15 years old uncompleted, hospitalized with a confirmed diagnosis of COVID-19. Methodology: Cross-sectional, quantitative, retrospective study, through data collection of patients aged 0-5 incomplete, hospitalized with confirmed laboratory diagnosis of COVID-19, in a children's hospital in southern Brazil, in the period from June 1, 2020 on May 31, 2021, using information from SIVEP-flu forms and compulsory notification forms from the State of Santa Catarina. Results: Of the 69 patients hospitalized with COVID-19, 50.7% were female, with a mean age of 4.04 years. Mild symptoms were more common in 72.9% (n=41), predominant symptoms were fever 73.7% (n=28), cough 60.5% (n=23) and coryza 73.7% (n=28). ). Most were hospitalized in a ward bed, 78.2% (n=54) and were discharged, another 20.8% (n=15) needed an UTI bed. Of the patients admitted to the UTI, 21% (n=13) had moderate/severe/critical symptoms and of these (n=2) died. Conclusion: The most affected age group was 0 to 3 years old, and female. The mildest respiratory symptoms were the most common, with fever and cough being the most prevalent, only 2 patients died. Laboratory tests showed a predominance of leukocytosis and lymphopenia, and increased C-reactive protein. In imaging exams, there was a predominance of diffuse interstitial infiltrates, followed by ground-glass opacity, especially in patients who were in the UTI. Keywords: COVID-19, respiratory infection, pediatrics, SARS-CoV-2, epidemiology.